2020
DOI: 10.1063/5.0009768
|View full text |Cite
|
Sign up to set email alerts
|

Study on helium atmospheric pressure plasma jet using collisional-radiative model

Abstract: The helium (He) non-thermal atmospheric pressure plasma jet (APPJ) source was configured, and the He spectra were measured by applying AC power to the source. A He collisional-radiative (CR) model was developed to investigate the He spectra obtained from the APPJ source. Different atmospheric pressure (AP) processes were evaluated, and the dominant processes among them that contribute to the He spectra were determined. The plasma parameters of the APPJ were determined using the He CR model, and the He spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The line intensity ratio (LIR) method combined with the He collisional-radiative (CR) model for an APPJ was applied in this study. [24] Using the CR model, the electron temperature and density in Section A were calculated to be 1.3-1.8 eV and 1.6-2.5 × 10 12 cm −3 , respectively, for which the LIRs of 3 1 D-2 1 P (667.8 nm)/3 1 S-2 1 P (728.1 nm), 3 1 S-2 1 P (728.1 nm)/3 3 S-2 3 P (706.5 nm), and 3 3 D-2 3 P (587.6 nm)/3 3 S-2 3 P (706.5 nm) were selected. The electron temperature and density determined using the continuum radiation were slightly lower than those computed using the CR model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The line intensity ratio (LIR) method combined with the He collisional-radiative (CR) model for an APPJ was applied in this study. [24] Using the CR model, the electron temperature and density in Section A were calculated to be 1.3-1.8 eV and 1.6-2.5 × 10 12 cm −3 , respectively, for which the LIRs of 3 1 D-2 1 P (667.8 nm)/3 1 S-2 1 P (728.1 nm), 3 1 S-2 1 P (728.1 nm)/3 3 S-2 3 P (706.5 nm), and 3 3 D-2 3 P (587.6 nm)/3 3 S-2 3 P (706.5 nm) were selected. The electron temperature and density determined using the continuum radiation were slightly lower than those computed using the CR model.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that the electron temperature in an APPJ is less than 4 eV, and the electron density is sufficiently large to distinguish the continuum radiation in the plasma spectra. [21,24,40,41] Therefore, optical diagnostics using continuum radiation can be appropriate for determining the electron temperature and density of an APPJ.…”
Section: Emissivity Of Continuum Radiation Via Breamsstrahlung In Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Many applications of APPJs rely on the plasma production of active species [17,18] which is dependent on several parameters including the electric field strength [19][20][21]. While the knowledge of APPJs has advanced considerably [1], the characteristics of APPJs, such as optical emission, electron density, electron temperature and electric field strength, are still actively investigated [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The CR model for neutral helium was further improved by Goto [25]. This model was also used by several researchers to study helium non-thermal atmospheric-pressure plasma jet [26]. The CR model of the ADAS code and database has been used for the study of the laser plasma, the tokamak plasma, etc.…”
mentioning
confidence: 99%